Rozwiąż równania; a)8x=3x+15 b)2(x+2)=2x+4 c)5x+1=x+2(1+2x) d)x+6=2x+4=4-3x f)3x+11=6x-1 g)2(x- 1)=3x-x h)-(5+x)+2=2(3x) i)2(x+3)-4(2x-2)=6x-4 j)4x-3(3x-5)=2x k)0,3x-2,4=1,5x+1,8 l)0,4+2,3x=2,5x-4 ł)0,6x4,8=5x+11 m)(ułamki)x/3+x/2+2=5 n)x/4+x/3+16=x o)⅔x-3=2x+10/4 p)x-1/ 2-x4+4/ 3=2x r)¾x-4x+1/ 2+x=-⅜ s)5x-11/ 4-x-1/ 10=11x-1/ 12 t)x+3/ 2=x-5/ 4

3

Odpowiedzi

2010-02-19T16:26:01+01:00
A) 5x=15 /5
x=3
b)2x+4=2x+4
2x-2x=4-4
0
c)5x+1=x+2+4x
5x-x-4x=2-1
0=1
d)x+6=2x+4=4-3x
x-2x=4-6=4-3x
-x=-2=4-3x
-x+3x=4+2
2x=6
x=3
e)3x+11=6x-1
-3x=-12
x=4
f)2x-2=3x-x
2x-3x+x=2
-x+x=2
0=2
g)-5-x+2=6x
-3=7x
x=-3/7
i)2(x+3)-4(2x-2)=6x-4
2x+6-8x+8=6x-4
-2x+14=6x-4
-8x=-18
x=18/8
j)4x-3(3x-5)=2x k)0,3x-2,4=1,5x+1,8
4x-9x+15=2x 0,3x-1,5x=1,8+2,4
-7x=-15 -1,2x=4,2
x=15/7 x=-3,5

m)0,4+2,3x=2,5x-4

-0,2x=-4,4
x=22

ł)0,6x4,8=5x+11 brakuje znaku

m)(ułamki)x/3+x/2+2=5

x/3+x/2=3 /*6
2x/6+3x/6=18
5x/6=18 / *6
5x=108
x=21,6
n)x/4+x/3+16=x /*12
3x/12+4x/12+192=12x /*12
3x+4x-144x=192
-137x=192
x=-192/137




2010-02-19T16:31:31+01:00
A)8x=3x+15
8x-3x=15
5x=15
x=3
b)2(x+2)=2x+4
2(x+2)=2(x+2)
0x=0 x nalezy do R
c)5x+1=x+2(1+2x)
5x+1=x+2+4x
0x=1 sprzeczne
d)x+6=2x+4=4-3x
x-2x+6-4=4-3x
-x+2=4-3x
-2x=-2
x=1
f)3x+11=6x-1
3x-6x=-1-11
-3x=-12
x=4
g)2(x- 1)=3x-x
2x-2=3x-x
0x=2 sprzeczne
h)-(5+x)+2=2(3x)
-5-x+2=6x
-x-3=6x
-7x=3
x=-3/7
i)2(x+3)-4(2x-2)=6x-4
2x+6-8x+8=6x-4
-6x+14=6x-4
-12x=-18
x=3/2
j)4x-3(3x-5)=2x
4x-9x+15=2x
-5x-2x=-15
-7x=-15
x=15/7
k)0,3x-2,4=1,5x+1,8
-1,2x=4,2
x=-3,5
l)0,4+2,3x=2,5x-4
-0,2x=-4,4
x=22
ł)0,6x+4,8=5x+11
-4,4x=6,2
x=-6,2/4,4
m)(ułamki)x/3+x/2+2=5
2x+3x+12=30
5x=18
x=3,6
n)x/4+x/3+16=x
3x+4x+192=12x
-5x=-192
x=38,4
o)⅔x-3=2x+10/4
8x-36=24x+30
-16x=66
x=-4,125
p)x-1/ 2-x4+4/ 3=2x
3x-3-8x-8=12x
-17x=11
x=-11/17
r)¾x-4x+1/ 2+x=-⅜
6x-32x+4+8x=-3
-18x=-7
x=7/18
s)5x-11/ 4-x-1/ 10=11x-1/ 12 napisz to inaczej
t)x+3/ 2=x-5/ 4
2x+6=x-5
x=-11
  • Użytkownik Zadane
2010-02-19T16:35:07+01:00
A)8x=3x+15
5x=15
x=3

b)2(x+2)=2x+4
2x+4=2x+4
0=0

c)5x+1=x+2(1+2x)
5x+1=x+2+4x
5x+1=5x+2
0≠1

f)3x+11=6x-1
-3x=-12
x=4

g)2(x- 1)=3x-x
2x-2=2x
0≠2

h)-(5+x)+2=2(3x)
-5-x+2=6x
3-x=6x
3=7x
x=³/₇

i)2(x+3)-4(2x-2)=6x-4
2x+6-8x+8=6x-4
-6x+14=6x-4
-12x=10
x=-¹⁰/₁₂=-⁵/₆

j)4x-3(3x-5)=2x
4x-6x+15=2x
-2x+15=2x
-4x=-15
x=¹⁵/₄=3¾

k)0,3x-2,4=1,5x+1,8
-1,2x=4,2
x=-3,5

l)0,4+2,3x=2,5x-4
-0,2x=-3,6
x=18

m)x/3+x/2+2=5 /*6
2x+3x+12=30
5x=18
x=¹⁸/₅=3⅗

n)x/4+x/3+16=x /*12
3x+4x+192=12x
7x+192=12x
-5x=-192
x=38⅖

o)⅔x-3=2x+¹⁰/₄ /*12
8x-36=24x+30
-18x=-6
x=⁶/₁₈=⅓

t)x+3/ 2=x-5/ 4 /*4
2x+6=x-5
x=-11